2021
DOI: 10.1038/s41598-021-98479-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of elevated serum fatty acid synthase in chronic limb-threatening ischemia

Abstract: There are currently no serum-based evaluations that can corroborate the severity of peripheral artery disease (PAD). In this cross-sectional study, we assessed the prevalence of elevated serum fatty acid synthase (cFAS) in patients with chronic limb-threatening ischemia (CLTI) and evaluated the accuracy of its use in detecting this condition. Preoperative fasting serum samples from 87 patients undergoing vascular intervention were collected between October 2014 and September 2016. Median age was 62 years, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Our study observed different gene expression patters of ppara, acox1, and cpt1a in carotid and lower extremity arterial tissue, suggesting that atherosclerotic disease progression is unlikely homogeneous. We similarly observed that other critical lipid mediators are differentially expressed and activated in carotid and lower extremity arterial tissue (23,46,47). For example, choline-ethanolamine phosphotransferase 1 (CEPT1), a key regulator of de novo phospholipogenesis, is highly expressed in Min-diseased carotid arterial segments particularly in individuals with diabetes (22).…”
Section: Discussionmentioning
confidence: 80%
“…Our study observed different gene expression patters of ppara, acox1, and cpt1a in carotid and lower extremity arterial tissue, suggesting that atherosclerotic disease progression is unlikely homogeneous. We similarly observed that other critical lipid mediators are differentially expressed and activated in carotid and lower extremity arterial tissue (23,46,47). For example, choline-ethanolamine phosphotransferase 1 (CEPT1), a key regulator of de novo phospholipogenesis, is highly expressed in Min-diseased carotid arterial segments particularly in individuals with diabetes (22).…”
Section: Discussionmentioning
confidence: 80%
“…Naturally, we also observed serum samples that had very high LDL (>180 mg/dL), while others that had low LDL (<90 mg/dL). Since it was previously reported that there was no correlation between cFAS and LDL content in human serum, we intentionally evaluated the impact of human serum samples with either high and low cFAS or LDL 21 . Like others who demonstrated that LDL alone does not cause macrophage foam cell formation, we also observed that macrophages conditioned with serum containing high LDL, but low cFAS, did not lead to foam cell formation [52][53][54][55] .…”
Section: Discussionmentioning
confidence: 99%
“…Serum LDL content was determined by the Washington University in St. Louis Core Laboratory for Clinical Studies (CLCS), utilizing a N-Geneous® LDL cholesterol kit (Sekisui Diagnostics, #7120) using a Roche Cobas c501 analyzer. Serum cFAS content was determined using commercial ELISA according to manufacturer's instructions (Aviva, OKEH04869) 21,22,26 . Following conditioned media treatments, macrophages were also lysed with standard freeze thaw method in PBS and lysates were standardized to protein concentration using Bradford Protein Assay.…”
Section: Human Serummentioning
confidence: 99%
See 2 more Smart Citations